The effect of selected buffering agents on performance in the competitive 1600 meter run - Avedisian, L.; Guerra, A.; Wilcox, A.; Fox, S. (Medicine & Science in Sports & Exercise, 1995)
Five male and four female trained track athletes, between the ages of 18 and 30, participated in a total of four competitive 1600 m races scheduled at least three days apart. Ss ingested a treatment (400 mg/kg NaHCO3 or 500 mg/kg sodium citrate) or placebo (calcium carbonate) 2 hours prior to three of the races; one race was used as a control. Order of treatments was randomized. The buffering agents had no effect on racing time. Bicarbonate loading was associated with uncomfortable side effects in the majority of athletes. Implication. Bicarbonate loading should be practiced several times before determining if it can be tolerated. Even then there is no guarantee that it will improve 1600 m running race performances.